Game Theoretic Risk Analysis of Security Threats - Bier, Vicki M. M.; Azaiez, M. Naceur; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2009)
Game Theoretic Risk Analysis of Security Threats introduces reliability and risk analysis in the face of threats by intelligent agents. More specifically, game-theoretic models will be developed for identifying optimal and/or equilibrium defense and attack strategies in systems of varying degrees of complexity. The book covers applications to networks, including problems in both telecommunications and transportation. However, the book$1 (Bs primary focus is to integrate game theory and reliability methodologies into unified techniques to predict, detect, diminish, and stop intentional attacks at targets that vary in complexity. In this book, leading researchers combine reliability and risk analysis with game theory methods to create a set of functional tools that can be used by security personnel to offset intentional, intelligent threats (including the threats of terrorism and war). This means a comprehensive treatment of such problems must consider two aspects: (1) the structure of the system to be protected and (2) the adaptive nature of the threat (that is, beyond the static nature of the threat). The book provides a set of scientific tools for analyzing and applying game-theoretic reliability problems in the presence of intentional, intelligent threats. These scientific tools address problems of global safety and create more cost-effective defensive investments. .s
Why Both Game Theory and Reliability Theory Are Important in Defending Infrastructure against Intelligent Attacks -- Game Theory Models of Intelligent Actors in Reliability Analysis: An Overview of the State of the Art -- Optimizing Defense Strategies for Complex Multi-State Systems -- Defending Against Terrorism, Natural Disaster, and All Hazards -- A Bayesian Model for a Game of Information in Optimal Attack/Defense Strategies -- Search for a Malevolent Needle in a Benign Haystack -- Games and Risk Analysis: Three Examples of Single and Alternate Moves -- Making Telecommunications Networks Resilient against Terrorist Attacks -- Improving Reliability through Multi-Path Routing and Link Defence: An Application of Game Theory to Transport.
Keywords: Engineering; Operations research; Decision making; Applied mathematics; Engineering mathematics; Game theory; Industrial engineering; Production engineering; Quality control; Reliability; Industrial safety; Engineering; Quality Control, Reliability, Safety and Risk; Game Theory, Economics, Social and Behav. Sciences; Applications of Mathematics; Industrial and Production Engineering; Operation Research/Decision Theory; Operating Procedures, Materials Treatment; Electronic books